2007
DOI: 10.1097/brs.0b013e318074d62e
|View full text |Cite
|
Sign up to set email alerts
|

MR T2 Image Classification in Cervical Compression Myelopathy

Abstract: Preoperative ISI on T2-weighted sagittal MRI was correlated with patient age, duration of disease, postoperative JOA score, and postoperative recovery rate. Patients with the greatest ISI had the worst postop erative recovery. Classification of ISI can be a predictor of surgical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
123
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(134 citation statements)
references
References 8 publications
5
123
2
1
Order By: Relevance
“…Statistical analysis showed significant difference in recovery rates between different grades of T2 signal intensity changes. Recovery rate decreased significantly grade 0 to grade 2.These data were consistent with the study Yasutsugu et al 11 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Statistical analysis showed significant difference in recovery rates between different grades of T2 signal intensity changes. Recovery rate decreased significantly grade 0 to grade 2.These data were consistent with the study Yasutsugu et al 11 .…”
Section: Discussionsupporting
confidence: 82%
“…Statistical analysis showed significant difference in preoperative mJOA score between these groups. In the study by Yasutsugu et al 11 , there was no significant difference in the preoperative score between different grades of T2 signal intensity changes. Mean postoperative JOA score was 13.…”
Section: Discussionmentioning
confidence: 99%
“…13,16,17 However, contrary to expectation, there was no existence of statistically significant correlation (P = 0.067) between GSI and TA preoperatively. The reasons for this result could be resulted from strong influence of other variance such as age, differences in populations, site of compression and duration of symptoms.…”
Section: Discusioncontrasting
confidence: 48%
“…It has been reported that those signal intensity changes are associated with a poor neurological prognosis after decompression surgery for CSM. [12][13][14][15] On the other hand, Tauchi et al 16 recently reported that the MRI findings of the spinal cord were not associated with the surgical outcome in CSA patients, and they speculated that the compression or damage in the cervical spine was localized in the anterior horn of the spinal cord or the ventral nerve root in affected CSA patients, although it exists in the central portion of the spinal cord in most CSM patients. In the present study, we investigated the association between the signal intensity changes of the spinal cord on T2-weighted MR images and the neurological prognosis not only at the final observational follow-up, but also at the final follow-up after conversion to surgery, and we showed that CSA patients with high signal intensity changes on T2-weighted MRI had a poorer neurological prognosis compared with those without the high signal intensity change, although no significant difference was noted when the analysis was limited to the patients who required conversion to surgery.…”
Section: Discussionmentioning
confidence: 99%